2019
DOI: 10.3390/ani9070426
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Citrus limon Powder as a Natural Feed Supplement to Boost the Productive Performance, Antioxidant Status, and Blood Biochemistry of Growing Rabbits

Abstract: The current study examined the influence of Citrus limon (dry lemon) on the hemato-biochemical profiles, and antioxidant indices of growing rabbits. Forty-eight growing New Zealand White rabbits (age, eight weeks; weight, 1543.33 ± 25 g) were allocated into three groups (16 animals each), the first group was (control) fed a basal diet, whereas the second and third groups were supplemented with dried lemon, 1% or 2% DLP, respectively. A GC-MS analysis of more than 27 active constituents was performed. Feed conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Other studies indicated an increase in some productive performance parameters, such as Khalid et al [28] who observed that Moringa oleifera leaf powder increased daily gain and improved the feed rate conversion. In another study, Elwan et al [29] fed rabbits with 1 and 2% of Citrus limon powder and found that the parameters related to final weight, weight gain, and average daily gain all increased. Perhaps, P. dulce fruits did not improve productive performance, but they can be used to feed rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated an increase in some productive performance parameters, such as Khalid et al [28] who observed that Moringa oleifera leaf powder increased daily gain and improved the feed rate conversion. In another study, Elwan et al [29] fed rabbits with 1 and 2% of Citrus limon powder and found that the parameters related to final weight, weight gain, and average daily gain all increased. Perhaps, P. dulce fruits did not improve productive performance, but they can be used to feed rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…( Ahmad et al, 2019 ) which were also recommended by the informants as anti-hypothyroid treatment. Miler et al (2017) and Elwan et al (2019) have demonstrated that Citrus limon (L.) Osbeck flavanones naringenin and hesperetin, administrated orally (15 mg/kg) during four weeks as effective antioxidants, significantly inhibited lipid peroxidation and increased serum TSH in male Wistar rats. Besides, Chaturvedi et al (1993) have reported a slight stimulation of the thyroid gland by the alcoholic extract of Saussurea lappa (Decne.)…”
Section: Discussionmentioning
confidence: 99%
“…The high concentration of flavonoids makes the lime peel has potential antibacterial and antioxidant. 21 The mechanism of essential oils in inhibiting and killing microorganisms is associated with their interactions with hydrophobic microorganisms, which causes the oil to be partitioned on the lipid bilayer cell membrane, which will affect the respiratory chain thus causes the leakage of bacterial cell contents. The weakness of the bacterial enzyme system can also be a potential mechanism of action.…”
Section: Discussionmentioning
confidence: 99%